(untitled) (Estudos em Design, 2019)
Quadro editorial Editores Cristina Portugal Rita Maria de Souza Couto Avaliadores desta edição v. 27, n. 1 (2019) Alexandre Santos de Oliveira Álvaro José Barbosa Sousa Ana Veronica Pazmino Antonio Ferreira Colchete Filho Cássia Letícia Carrara Cristina Portugal Daniel Lourenço Daniel Portugal Daniel Raposo Daniel Wyllie Lacerda Rodrigues Denise Dantas Edson Rufino de Souza Eloiza Andrade Corrêa Fernando Martins Frederico Braida Gabriel Patrocínio Giselle Merino Haroldo Gallo Irina Aragão dos Santos Juliana Bueno Lais Licheski Leticia Affini Letícia Pedruzzi Fonseca Linda Linn Luiz Agner Luiza Novaes Marcos Beccari Marcos Braga Maria José Jorente Mariano Lopes de Andrade Neto Maristela Mitsuko Ono Marizilda Menezes Rogério José Câmara Sandra Regina Rech Stephania Padovani Tiago Barros Pontes Silva Virginia Borges Kistmann Walter Dutra da Silveira Neto